2022
DOI: 10.1111/sode.12578
|View full text |Cite
|
Sign up to set email alerts
|

How being observed influences preschoolers’ emotions following (less) deserving help

Abstract: Children sometimes show positive emotions in response to seeing others being helped, yet it remains poorly understood whether there is a strategic value to such emotional expressions. Here, we investigated the influence seeing a peer receive deserving help or not on children's emotions, which were assessed while the peer was present or not. To measure children's emotional expression, we used a motion depth sensor imaging camera, which recorded children's body posture. Five‐year‐old children (N = 122) worked on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Importantly, it is not children’s elevated posture per se that reflected positive emotions but rather the direction of the effects was such that positive outcomes, which are generally associated with positive emotions, resulted in elevated body posture. In contrast, negative events such as failing to achieve a goal 42 , 58 , receiving undeserving rewards 51 , 59 , or making unjustified requests for help 52 resulted in lowered body posture.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, it is not children’s elevated posture per se that reflected positive emotions but rather the direction of the effects was such that positive outcomes, which are generally associated with positive emotions, resulted in elevated body posture. In contrast, negative events such as failing to achieve a goal 42 , 58 , receiving undeserving rewards 51 , 59 , or making unjustified requests for help 52 resulted in lowered body posture.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, success at a difficult task or failure at an easy task have been shown to induce changes in children’s body posture at three years of age 49 , highlighting consistency in the findings across the life span 42 . show that 2-year-old children display increased positive emotions, indicated by more upright body posture, when they successfully achieve a goal for themselves or when they successfully help someone else achieve a goal—but posture is lower if no goal is achieved for anyone (see 51 , 52 for similar applications of the measure). The authors particularly stress the link between body posture and emotional expression and highlight the possibility that task success could trigger increased positive emotions which is reflected in elevated body posture.…”
Section: Introductionmentioning
confidence: 99%
“…This could for instance be the case if children's upper body posture varies due to crouching, jumping or running. A recent body of work has shown that children's change in chest expansion is a valid index of the valence of children's emotional response [ 52 , 61 ]. For instance, in one study, the patterns for children's change in chest expansion were similar to those for emotion valence ratings provided by adult coders (Study 1, [ 52 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Children may risk being viewed as more concerned for their own gains even if it comes at a cost to others. In the context of cooperation, signalling one's fear of a peers' evaluation and rejection, for example, through loweredbody posture, may have an adaptive value for children who aspire to good terms with their peers (see also Gerdemann, Büchner, & Hepach, 2022b).…”
Section: Fear Can Promote Competition Defensive Aggression and Domina...mentioning
confidence: 99%